USING BLOOM’S TAXONOMY AND GENDER DIFFERENCES TO ENHANCE THEORY AND PRACTICE IN GLOBAL EDUCATION - Belhamidi, Hadjer; Mazouzi, Amina; Yamin, Boulenouar Mohammed (Proceedings of the International Conference on Education, 2017)
Gender differences are important in theory vs. practice in education, and ignoring them causes the problem of incongruity instead of harmony with the material learnt. Psychiatrists have discovered a difference in the way the two genders handle theoretical and applied knowledge. This difference lies in genders’ performance, whether they learn the theory alone, or practice what they learn. We will investigate how Bloom’s Taxonomy (used by curriculum designers), particularly the psychomotor approach, would be misused by curriculum designers if they ignore the different patterns of reasoning and application of the two genders. Psychiatrists have discovered that females understand the theoretical knowledge better than the males, while the males on the other hand perform the application of the applied knowledge better than the females. As a result, countries/ schools/ syllabus designers that focus on theory more than they do on practice end up with a higher number of female students in schools, while the males tend to lose interest and drop out somehow. The same result occurs with majors that focus on theory alone, as literature, history, languages…etc. This research urges curriculum designers to consider gender differences in applying the psychomotor approach. The research analyzes how far curriculums consider application in order to help curriculum designers face problems at the level of gender differences. Researchers will find this study useful to understand how to use theory and practice to raise the level of students’ performance in various majors